2021
DOI: 10.1093/cid/ciab104
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Severe Acute Respiratory Syndrome Coronavirus 2 Infection on Pregnancy Outcomes: A Population-based Study

Abstract: Background A population-based study to describe the impact of SARS-CoV-2 infection on pregnancy outcomes. Methods Prospective, population-based study including pregnant women consecutively attended at first/second trimester or at delivery at three hospitals in Barcelona, Spain. SARS-CoV-2 antibodies (IgG and IgM/IgA) were measured in all participants and nasopharyngeal RT-PCR was performed at delivery. The primary outcome was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
109
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(126 citation statements)
references
References 27 publications
14
109
1
2
Order By: Relevance
“…First, we showed that pregnant women with SARS-CoV-2 infection had elevated levels of IgM and IgG in the peripheral circulation, whereas only IgG was detectable in the cord blood of their neonates, suggesting that acute fetal infection did not occur. This finding is consistent with several reports showing that IgM is undetected in the cord blood of neonates born to women with SARS-CoV-2 infection 29,42,43 . However, few studies have demonstrated that both IgM and IgG are detectable in a small fraction of neonates born to women diagnosed with COVID-19 16,24,30 .…”
Section: Discussionsupporting
confidence: 93%
“…First, we showed that pregnant women with SARS-CoV-2 infection had elevated levels of IgM and IgG in the peripheral circulation, whereas only IgG was detectable in the cord blood of their neonates, suggesting that acute fetal infection did not occur. This finding is consistent with several reports showing that IgM is undetected in the cord blood of neonates born to women with SARS-CoV-2 infection 29,42,43 . However, few studies have demonstrated that both IgM and IgG are detectable in a small fraction of neonates born to women diagnosed with COVID-19 16,24,30 .…”
Section: Discussionsupporting
confidence: 93%
“…A possible overestimation of the risk magnitude of obstetric complications in COVID-19 pregnancies could be partially related to the bias and the relative low level of evidence of first case reports and case series, published by a stressed scientific community, committed to publish clear data to provide knowledge to approach the overwhelming outbreak period of the pandemic. Since then, much data regarding the impact of COVID-19 in pregnancy has been accumulated [58,[65][66][67]. To date, data available about the consequences of COVID-19 in pregnancy outcomes state that preterm delivery and fetal distress are the main adverse outcomes observed in symptomatic COVID-19 pregnancies in the third trimester and at delivery [59,[65][66][67].…”
Section: Previous and Current Coronavirus Infection Experience In Pregnant Womenmentioning
confidence: 99%
“…Since then, much data regarding the impact of COVID-19 in pregnancy has been accumulated [58,[65][66][67]. To date, data available about the consequences of COVID-19 in pregnancy outcomes state that preterm delivery and fetal distress are the main adverse outcomes observed in symptomatic COVID-19 pregnancies in the third trimester and at delivery [59,[65][66][67]. The effects of SARS-CoV-2 in the first and second trimesters deserve specific studies to elucidate the controbution of the infection in complications such miscarriage, preeclampsia or IUGR showing variable and inconclusive incidence among published studies [65,[67][68][69][70][71].…”
Section: Previous and Current Coronavirus Infection Experience In Pregnant Womenmentioning
confidence: 99%
See 2 more Smart Citations